Experimental study on catalytic pyrolysis of oily sludge for H2 production under new nickel-ore-based catalysts. (15th June 2022) - Zhang, Xitong; Xu, Jiayu; Ran, Shuai; Gao, Ying; Lyu, Yinong; Pan, Yueshen; Cao, Fei; Lin, Yunhao; Yang, Zixu; Wang, Zhongxian; Guo, Dandan; Wang, Qi; et al.
Abstract: Oily sludge (OS) from steel mills contains a large number of heavy components and has high viscosity. In this paper, the preparation of high value-added gas from the pyrolysis of OS catalyzed by calcined olivine (C-OL), xiuyan jade (C-XY), iddingsite (C-ID) and their nickel carrier was investigated. ICP-OES, SEM, EDX, XRF, and XRD were applied to characterize the catalysts. The effect of the catalyst on the pyrolysis of OS and the regulation mechanism of gas product quality were investigated. Thermogravimetric results showed that all the six catalysts could improve the total weight loss of OS, among which the addition of C-OL(Ni) increased by 11.58 wt%. Compared with the pyrolysis of OS, the production of H2 increased by 82.65 and 23.49 mL after C-OL and C-XY were added at 900 °C, respectively. Ni ore-based catalysts can promote tar cracking, thereby producing more pyrolysis gas, in which the production of H2 is significantly increased. The addition of C-XY(Ni) increased the production of H2 by 239.29 mL. After nickel was loaded, the catalysts showed better catalytic activity at a high temperature. Results show that the nickel-loaded natural ore as catalyst can promote the pyrolysis of OS and can obtain pyrolysis gas with high added value. Graphical abstract: Image 1 Highlights: The catalytic pyrolysis of oily sludge was employed with six different catalysts. Ni ore-based catalysts promoted pyrolysis of oily sludge to produce hydrogen. Calcined-xiuyan jade loaded with Ni(C-XY(Ni)) showed the best catalytic ability. After adding C-XY(Ni), the maximum gas yield was 1322 mL and the H2 accounted for 45%.